Molecular separation by using active and passive microfluidic chip designs: A comprehensive review - ALARÇİN, EMİNE (My University, 2023)
Separation and identification of molecules and biomolecules such as nucleic acids, proteins, and polysaccharides from complex fluids are known to be important due to unmet needs in various applications. Generally, many different separation techniques, including chromatography, electrophoresis, and magnetophoresis, have been developed to identify the target molecules precisely. However, these techniques are expensive and time consuming. \"Lab-on-a-chip\" systems with low cost per device, quick analysis capabilities, and minimal sample consumption seem to be ideal candidates for separating particles, cells, blood samples, and molecules. From this perspective, different microfluidic-based techniques have been extensively developed in the past two decades to separate samples with different origins. In this review, \"lab-on-a-chip\" methods by passive, active, and hybrid approaches for the separation of biomolecules developed in the past decade are comprehensively discussed. Due to the wide variety in the field, it will be impossible to cover every facet of the subject. Therefore, this review paper covers passive and active methods generally used for biomolecule separation. Then, an investigation of the combined sophisticated methods is highlighted. The spotlight also will be shined on the elegance of separation successes in recent years, and the remainder of the article explores how these permit the development of novel techniques.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarım Alet ve Makineleri; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Agricultural Tools and Machines; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, MEKANİK; MALZEME BİLİMİ, KOMPOZİTLER; Engineering, Computing & Technology (ENG); ENGINEERING; MATERIALS SCIENCE; ENGINEERING, MECHANICAL; MATERIALS SCIENCE, COMPOSITES; Malzemelerin mekaniği; Fizik Bilimleri; Makine Mühendisliği; Mechanics of Materials; Physical Sciences; Mechanical Engineering; active separation; biomolecule separation; hybrid separation; lab-on-a-chip; microfluidics; passive separation